User's guide to ASTM specification C 94 on ready-mixed concrete - Daniel, D. Gene; Lobo, Colin L. (ASTM manual series MNL 49, 2005)
Preface -- Introduction -- Scope -- Referenced Documents -- Basis of Purchase -- Ordering Information -- Materials -- Tolerances in Slump -- Air-Entrained Concrete -- Measuring Materials -- Batching Plant -- Mixers and Agitators -- Mixing and Delivery -- Use of Nonagitating Equipment -- Batch ticket Information -- Plant Inspection -- Practices, Test Methods, and Reporting -- Sampling and Testing Fresh Concrete -- Strength -- Failure to Meet Strength Requirements -- Keywords -- Annex (Mandatory information) -- References -- Appendix--ASTM C 94-35.